2012
DOI: 10.1021/jp3101865
|View full text |Cite
|
Sign up to set email alerts
|

Noble Gas Separation using PG-ESX (X = 1, 2, 3) Nanoporous Two-Dimensional Polymers

Abstract: Using planewave pseudopotential density functional theory and classical molecular dynamics simulations, we investigate the transport of noble gases through a family of two-dimensional hydrocarbon polymer membranes that generalize the “porous graphene” (PG) material synthesized by Bieri et al. by insertion of (E)-stilbene (ES) groups. We find that density functional theory overestimates the barrier height and empirical dispersion corrections underestimate the barrier height, compared to reference MP2/cc-pVTZ ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 59 publications
5
67
0
Order By: Relevance
“…S1) even if we do not consider that this effect can alter significantly the very favourable He/CH 4 and Ne/CH 4 probability ratios we have found. Further effects due to the neglect of both the interaction and competition of single components in the gas mixtures are not expected to provide significant deviations 13 in the obtained S behavior at least around and above room temperature.…”
Section: Force Fields and Quantum Dynamical Simulationsmentioning
confidence: 96%
See 2 more Smart Citations
“…S1) even if we do not consider that this effect can alter significantly the very favourable He/CH 4 and Ne/CH 4 probability ratios we have found. Further effects due to the neglect of both the interaction and competition of single components in the gas mixtures are not expected to provide significant deviations 13 in the obtained S behavior at least around and above room temperature.…”
Section: Force Fields and Quantum Dynamical Simulationsmentioning
confidence: 96%
“…The successful synthesis of these materials has led to important theoretical studies devoted, firstly, to their application as effective single-layer membranes for gas separation and water filtration technologies [7][8][9][10][11] and, secondly, to the tailoring of related porous 2D structures by changing pore shape and size through the incorporation of functional groups. [12][13][14][15] In this work we want to assess the capability of the recently synthesized graphdiyne and 2DPPH materials as efficient membranes for helium separation applications. As it is well known, helium is an irreplaceable natural resource and its growing demand in a variety of industrial and scientific applications, together with ongoing production deficiencies, has recently led to shortages of this element.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we assumed a classical Boltzmann distribution for the velocities of both 3 He and 4 He as suggested by previous studies [19,20,22,43,44]. This strategy not only provides a more conservative estimation of 3 He/ 4 He selectivity, but also avoids the complexity of dealing with a mixed nonideal quantum gas composed of fermionic 3 Although the g-C 3 N 4 membrane exhibits great selectivity of 3 He at low temperature, the transmission probability is 10 -34 at 49 K (Fig.…”
Section: Separating 3 He From 4 Hementioning
confidence: 99%
“…An interesting theoretical study by Brockway and Schrier has shown that a graphene membrane model based on a previously synthesized graphene porous membrane can be used to separate He from natural gas. 226,227 The authors conclude that the porous graphene (E)-stilbene 1 material outperforms existing materials in terms of selectivity and permeance.…”
Section: Gas Phase Separationmentioning
confidence: 99%